2016
DOI: 10.1186/s12899-016-0026-z
|View full text |Cite
|
Sign up to set email alerts
|

Ryanodine-induced vasoconstriction of the gerbil spiral modiolar artery depends on the Ca2+ sensitivity but not on Ca2+ sparks or BK channels

Abstract: BackgroundIn many vascular smooth muscle cells (SMCs), ryanodine receptor-mediated Ca2+ sparks activate large-conductance Ca2+-activated K+ (BK) channels leading to lowered SMC [Ca2+]i and vasodilation. Here we investigated whether Ca2+ sparks regulate SMC global [Ca2+]i and diameter in the spiral modiolar artery (SMA) by activating BK channels.MethodsSMAs were isolated from adult female gerbils, loaded with the Ca2+-sensitive flourescent dye fluo-4 and pressurized using a concentric double-pipette system. Ca2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Furthermore, regulation of cochlear blood flow is essential for hearing and is important as a treatment strategy for the restoration of hearing loss in humans [ 1 , 2 ]. In addition, due to the high energy consumption of auditory conduction, the blood supply of the spiral modiolar artery (SMA) is considered essential for maintaining the function of the hearing device [ 3 ]. And studies on the inner ear circulatory system have confirmed that, on the one hand, the cochlear strong ability of blood flow autonomous regulation could ensure the blood supply of local tissues, and on the other hand, this ability could reduce the impact of the rapid changes of blood pressure and also maintain water and electrolyte balance in the local tissues of the cochlea [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, regulation of cochlear blood flow is essential for hearing and is important as a treatment strategy for the restoration of hearing loss in humans [ 1 , 2 ]. In addition, due to the high energy consumption of auditory conduction, the blood supply of the spiral modiolar artery (SMA) is considered essential for maintaining the function of the hearing device [ 3 ]. And studies on the inner ear circulatory system have confirmed that, on the one hand, the cochlear strong ability of blood flow autonomous regulation could ensure the blood supply of local tissues, and on the other hand, this ability could reduce the impact of the rapid changes of blood pressure and also maintain water and electrolyte balance in the local tissues of the cochlea [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that disorders in the circulatory system in the inner ear are closely linked to sudden deafness [1,2], Meniere’s disease [3], senile hearing loss [4], and ototoxicity-induced hearing loss [5]. Moreover, the blood supply of the spiral modiolar artery (SMA) is believed to play a vital role in maintaining the function of the auditory apparatus because of the high energy consumption of auditory conduction process [68].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, if abnormal changes occur in the SMA, such as vasospasm, this change would reduce or even completely interrupt the cochlear blood supply. This condition contributes to blood circulation disorders in the inner ear and cochlear dysfunction, such as dizziness, tinnitus, and other symptoms [8,10]. Hence, the blood supply of SMA may have a decisive impact on maintaining normal hearing [11].…”
Section: Introductionmentioning
confidence: 99%